Enhanced ablation resistance of HfB2-HfC/SiBCN ceramics under an oxyacetylene torch environment. (15th July 2021) - Zhu, Qishuai; Liao, Xingqi; Ao, Dongfei; Liang, Bin; Li, Daxin; Yang, Zhihua; Jia, Dechang; Zhou, Yu; Zhang, Tao; Gao, Chenguang; Huang, Yongjiang
Highlights: Hot-pressed HfB2 -HfC/SiBCN ceramics were first successfully fabricated. The mass and linear ablation rates of the HfB2 -HfC/SiBCN were 0.0025 mg/s and 0.0004 mm/s. The ablation mechanisms of HfB2 -HfC/SiBCN ceramics have been proposed. Abstract: To further improve the ablation resistance of SiBCN ceramics, nanosized HfB2 was introduced by mechanical alloying and subsequent reactive hot-pressing techniques to fabricate HfB2 -HfC/SiBCN multiphase ceramics. The mass and linear ablation rates of the 30 vol% HfB2 -HfC containing SiBCN ceramics under an oxyacetylene flame for 10 s were lower than those of ZrB2 -ZrN/SiBCN and SiBCN, reaching to 0.0025 mg/s and 0.0004 mm/s respectively. Even ablated for 60 s, no trace of cracks appeared on the ablation surface. Oxidation of ceramic matrix, denudation of oxides, erosion by the combustion flow and the re-oxidation of the exposed matrix governed the ablation process.